Perilaku Konsumen pada Keputusan Pembelian Tanaman Hias di Jakarta Selatan - Yodfiatfinda Yodfiatfinda; Anggun Wulan Rahayu (Institut Pertanian Bogor, 2024)
This research analyzes consumer behavior and its impact on the purchase decisions of ornamental plants at Taman Anggrek Ragunan, South Jakarta. The Taman Anggrek Ragunan is the largest ornamental center in Jakarta. During the COVID-19 pandemic, demand for ornamental plants at Taman Anggrek Ragunan decreased by 50%. This research aims to determine the characteristics of ornamental plant consumers and analyze consumer behavior and its impact on purchase decisions of ornamental plants at Taman Anggrek Ragunan, South Jakarta. Respondents in this research were ornamental plant consumers who made purchases at Taman Anggrek Ragunan and were selected using a non-purposive sampling technique. The data used in this research comprises primary data and secondary data. For qualitative data, we convert it using a Likert scale to be analyzed quantitatively. The data analysis method uses multiple linear regressions. The results of the research show that the factors that have a significant impact on the decision to purchase ornamental plants at Taman Anggrek Ragunan, South Jakarta, are personal factors and psychological factors, while social factors and cultural factors do not have a significant impact. Personal and cultural factors have more influence on purchasing decisions for male respondents than female respondents. The four variables influence respondents with a high school education level more than undergraduates. Meanwhile, based on income level, the influence of the variable is stronger for respondents with an IDR 4 million or less income. Keywords: consumer behavior, multiple linear regression, ornamental plants, purchasing decisions